Differential associations of alcohol use with ischemic heart disease mortality by socioeconomic status in the US, 1997-2018 - Zhu, Yachen; Llamosas-Falcón, Laura; Kerr, William; Puka, Klajdi; Probst, Charlotte (JAMA network open, 2024)
IMPORTANCE: People with low socioeconomic status (SES) experience greater burden from alcohol-attributable health conditions and mortality at equal levels of alcohol consumption compared with those with high SES. A U-shaped association has been established between alcohol use and ischemic heart disease (IHD), but no study has explored how such an association differs by SES in the US. - OBJECTIVE: To investigate how the association of alcohol use with ischemic heart disease mortality differs by SES in the general US population. - DESIGN, SETTING, AND PARTICIPANTS: This cohort study used record-linked, cross-sectional National Health Interview Survey data for US adults aged 25 years and older, covering 1997 to 2018 with mortality follow-up until 2019. Data analysis was performed from March to June 2023. - EXPOSURES: SES (operationalized using education attainment) and alcohol consumption were obtained from self-reported questionnaires. - MAIN OUTCOMES AND MEASURES: The outcome was time to IHD mortality or last presumed alive by December 31, 2019. Cox proportional hazard models were applied to evaluate the interaction of SES and alcohol use on IHD mortality, with age as the time scale. Sex-stratified analyses were performed, adjusting for race and ethnicity, marital status, smoking, body mass index, physical activity, and survey year. Fine-Gray subdistribution models were applied to account for competing risks. - RESULTS: This cohort study of 524035 participants (mean [SD] age at baseline, 50.3 [16.2] years; 290492 women [51.5%]) found a statistically significantly greater protective association of drinking less than 20 g per day (vs lifetime abstinence) with IHD mortality in the high-SES group compared with the low-SES group (interaction term hazard ratio [HR], 1.22 [95% CI, 1.02-1.45] in men; HR, 1.35 [95% CI, 1.09-1.67] in women). In addition, the differential associations of drinking less than 20 g per day with IHD mortality by SES were observed only among people with less than monthly heavy episodic drinking (HED) (interaction term, HR, 1.20 [95% CI, 1.01-1.43] in men; HR, 1.34 [95% CI, 1.08-1.67] in women); no difference was found in people with at least monthly HED. Among women there was a greater protective association of drinking less than 20 g per day with IHD mortality in the high-SES group than the middle-SES group (interaction term, HR, 1.35 [95% CI, 1.06-1.72]). Among men, the harmful association of drinking more than 60 g per day with IHD mortality in the low-SES group was largely explained by other behavioral risk factors (ie, smoking, body mass index, and physical activity). - CONCLUSIONS AND RELEVANCE: This cohort study found a greater protective association between drinking less than 20 g per day with less than monthly HED and IHD mortality in the high-SES group compared with the low-SES group, in both sexes even after adjusting for key covariables and behavioral risk factors. The findings suggest that public health interventions on alcohol use should account for different socioeconomic backgrounds when assessing the level of risk related to alcohol exposure, bearing in mind that levels of consumption deemed safe regarding a specific outcome such as IHD may indeed be less safe or not safe across all sociodemographic groups.
Gesehen am 29.07.2024